Microbial Transformation of Prenylquercetins by Mucor hiemalis - Han, Fubo (Molecules, 2020)
Quercetin, one of the most widely distributed flavonoids, has been found to show various biological activities including antioxidant, anticancer, and anti-inflammatory effects. It has been reported that bioactivity enhancement of flavonoids has often been closely associated with nuclear prenylation, as shown in 8-prenylquercetin and 5′-prenylquercetin. It has also been revealed in many studies that the biological activities of flavonoids could be improved after glucosylation. Three prenylated quercetins were prepared in this study, and microbial transformation was carried out in order to identify derivatives of prenylquercetins with increased water solubility and improved bioavailability. The fungus M. hiemalis was proved to be capable of converting prenylquercetins into more polar metabolites and was selected for preparative fermentation. Six novel glucosylated metabolites were obtained and their chemical structures were elucidated by NMR and mass spectrometric analyses. All the microbial metabolites showed improvement in water solubility.